Conocimientos, actitudes y prácticas de la salud bucal en escolares de la Unidad Educativa Dr. Edison Calle Loaiza de la ciudad de Loja - Mejía Vélez, Paulina Alexandra (2021)
One of the biggest challenges for dentistry is reaching high-risk groups such as children, it is important to publicize concepts and change oral hygiene habits. The objective of this research is "To assess the knowledge, attitudes and practices of oral health through traditional techniques in children of the basic education school" Dr. Edison Calle Loaiza ”; Longitudinal-cut evaluative study with a sample of 52 children aged 7 to 11 years, which was selected for convenience using the non-probability sampling technique, as an instrument a knowledge, attitudes and practices questionnaire was designed, consisting of 12 questions on knowledge, 9 questions to measure attitudes and 18 questions to evaluate oral health practices; The procedure involved a pre-test and a post-test after having instructed the study population for 10 weeks on basic oral health issues. For the interpretation of the results, the 50th percentile was established by dividing the sample into 2 equal parts, which allowed us to establish two categories for each variable, that is: adequate (> 50th percentile) and inadequate (<50th percentile). As a result, the following were obtained: the knowledge variable reached a p value of 0.00; Attitudes with a p-value of 0.011 compared to the results obtained in the practice variable with a p-value of 0.322 showed a slight improvement, although it is not statistically significant. Thus concluding that the children in the study did not improve their knowledge, attitudes, and practices in oral health significantly. Keywords: Likert, prevention, promotion, traditional techniques.